Historical Types of Economic Powers: Carthage – Venice – England (Economic and Political Thought, 2013)
The concept of a great power in the science of international relations originatesfrom a realistic paradigm based on the idea of power as a foundationof international relations. The analysis based only on this paradigm seemsto narrow the real research space. A presentation of the issue of countriesbeing great powers in an economic context may be an interesting proposal inthe analysis of change processes and development tendencies in internationalrelations. As an interdisciplinary research instrument, it lets us treat economicand political processes in an integral way. The article makes an attemptto analyze the historical type of an economic great power. The empiric, valuableresearch material was provided by the history of Carthage, Venice andEngland. The research results can serve as an instrument to explain presentphenomena and mechanisms taking place in the international environment.